The Effects of Job Embeddedness on Organizational Citizenship, Job Performance, Volitional Absences, and Voluntary Turnover - Lee, Thomas; Mitchell, Terence R.; Sablynski, Chris J.; Burton, James P.; Holtom, Brooks C. (Academy of Management Journal, 2004)
This study extends theory and research on job embeddedness, which was disaggregated into its two major subdimensions, on-the-job and off-the-job embeddedness. As hypothesized, regression analyses revealed that off-the-job embeddedness was significantly predictive of subsequent "voluntary turnover" and volitional absences, whereas on-the-job embeddedness was not. Also as hypothesized, on-the-job embeddedness was significantly predictive of organizational citizenship and job performance, whereas off-the-job embeddedness was not. In addition, embeddedness moderated the effects of absences, citizenship, and performance on turnover. Implications are discussed.